Answer:
![(y-6)^2=9](https://tex.z-dn.net/?f=%28y-6%29%5E2%3D9)
Step-by-step explanation:
Given
![y^2 - 12y = -27](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%3D%20-27)
Required
Get equivalent expression using completing the square
<em>Follow these steps:</em>
- <em>Take the coefficient of y; That is -12</em>
- <em>Divide it by 2; That is (-12/2)</em>
- <em>Square it: (-12/2)^2</em>
<em />
Add to both sides of the equation
![y^2 - 12y + (\frac{-12}{2})^2= -27 + (\frac{-12}{2})^2](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%2B%20%28%5Cfrac%7B-12%7D%7B2%7D%29%5E2%3D%20-27%20%2B%20%28%5Cfrac%7B-12%7D%7B2%7D%29%5E2)
![y^2 - 12y + (-6)^2= -27 + (-6)^2](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%2B%20%28-6%29%5E2%3D%20-27%20%2B%20%28-6%29%5E2)
![y^2 - 12y + 36= -27 + 36](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%2B%2036%3D%20-27%20%2B%2036)
![y^2 - 12y + 36= 9](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%2B%2036%3D%209)
Expand the right-hand side
![y^2 - 6y - 6y + 36= 9](https://tex.z-dn.net/?f=y%5E2%20-%206y%20-%206y%20%2B%2036%3D%209)
Factorize:
![y(y-6)-6(y-6) =9](https://tex.z-dn.net/?f=y%28y-6%29-6%28y-6%29%20%3D9)
![(y-6)(y-6)=9](https://tex.z-dn.net/?f=%28y-6%29%28y-6%29%3D9)
![(y-6)^2=9](https://tex.z-dn.net/?f=%28y-6%29%5E2%3D9)
The curve given has asymptotes at x=0 and y=0. We wish to move it right 7 units so the asymptote becomes x=7 and down 5 so the asymptote is y=-5
To move a function down 5 units subtract 5 from it. To move it right we subtract 7 from the independent variable (from the x). The new function is y=(3/(x-7))-5
y= (3 over (x-7)) then minus 5
Answer:
The answer is B.dividing 36.2 by ten thousands. Plz mark as the brainlyest answer.
Step-by-step explanation:
Answer:
Option A.
Step-by-step explanation:
According to triangle inequality theorem, a triangle exists if the sum of two sides is greater that third side.
Apply this theorem on each combination.
Case I:
...(1)
Case II:
...(2)
Case III:
...(3)
On combining (1), (2) and (3), we get
Therefore, the correct option is A.
Answer:
<h2>y = 2</h2>
Step-by-step explanation:
To find the value of y when x = 8 we must first find the relationship between the two variables.
The statement
y varies directly with variable x is written as
y = kx
where k is the constant of proportionality
when
x = 12
y = 3
Substitute the values into the above formula and solve for k
That's
3 = 12k
Divide both sides by 12
![k = \frac{1}{4}](https://tex.z-dn.net/?f=k%20%3D%20%20%5Cfrac%7B1%7D%7B4%7D%20)
So the formula for the variation is
![y = \frac{1}{4} x](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B1%7D%7B4%7D%20x)
when
x = 8
![y = \frac{1}{4} \times 8](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B1%7D%7B4%7D%20%20%5Ctimes%208)
we have the final answer as
<h3>y = 2</h3>
Hope this helps you